Unauthorized Polygamy and Legal Protection: A Pancasila-Islamic Sociological Jurisprudence Theory Analysis of Religious Court Judgments - Zahra Nur Fadzilah; Nasywa Syifa Salsabila; Ahmad Ashfannawa Fauza; Ahmad Muhamad Mustain Nasoha (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the phenomenon of unauthorized polygamy in Indonesia as a reflection of the gap between legal norms and social reality, with particular attention to its implications for women’s legal protection. Although Law No. 1 of 1974 requires court approval and spousal consent, such provisions are frequently bypassed, resulting in legal uncertainty and gender-based disadvantages. This research employs a normative qualitative approach using library research, analyzing statutory regulations, Religious Court decisions, and relevant scholarly literature through conceptual and case approaches. The findings reveal that unauthorized polygamy persists due to socio-cultural, economic, and religious factors, as well as weak law enforcement and inconsistent judicial reasoning. While some Religious Court decisions incorporate substantive justice considerations—such as women’s conditions, children’s welfare, and social impacts—others remain formalistic and procedural, leading to uneven legal protection. From the perspectives of Pancasila and Islamic Sociological Jurisprudence, this condition indicates that the law has not fully functioned as an instrument of social justice and public welfare (maslahah). The study concludes that strengthening women’s legal protection requires an integrated approach combining legal reform, judicial capacity development, and socio-legal awareness. Such efforts are essential to ensure that Islamic family law evolves toward a more equitable, context-sensitive, and justice-oriented system.